2022
DOI: 10.21511/imfi.19(4).2022.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender as a moderating variable on financial vulnerability using hierarchical regressions: Survey evidence from Indonesian traditional market traders

Abstract: Market traders have a significant contribution to GDP in Indonesia; however, their level of education is still low. This leads to a high level of financial vulnerability, so it is important to study this issue, and there is still not enough research on financial vulnerability. Market traders are considered to be more vulnerable to fraud and poor financial management, and this is more common among female traders who have a relatively high level of consumption and economic dependence on men. This study aims to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…High performance is one indicator of quality human resources (Kasmir: 2019). To attain its objectives, every organization must enhance the performance of its people resources (Hapsoro et al: 2022). As a result, human resources must be empowered through the use of Human Resource Management (Hasibuan: 2019).…”
Section: The Effect Of Discipline and Work Environment On Employee Pe...mentioning
confidence: 99%
“…High performance is one indicator of quality human resources (Kasmir: 2019). To attain its objectives, every organization must enhance the performance of its people resources (Hapsoro et al: 2022). As a result, human resources must be empowered through the use of Human Resource Management (Hasibuan: 2019).…”
Section: The Effect Of Discipline and Work Environment On Employee Pe...mentioning
confidence: 99%
“…Female managers have an affinity to be more cooperative and always in a state of readiness for inclusion in the development of consensus. Female managers are considered successful in adapting to challenging situations, can be comprehensive and very cooperative in strategic decision-making processes, and show a talent for balancing the interests of stakeholders to achieve the interests of all (Sims & Morris, 2018; Afolabi & Akinlolu, 2021; Hapsoro et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jagirani et al (2023) stressed the need to balance women and men on the board of directors. Hapsoro et al (2022) showed that only the presence of several women on the board of directors has a positive relationship with firm value. This study shows that women demonstrate better results in human resources management, business operations, strategic management, financial management, and marketing management.…”
Section: Verification Of Hypothesesmentioning
confidence: 99%